Circular RNA circ_0062019 exerts oncogenic properties in prostate cancer via mediating miR‐1253/NRBP1 axis. (6th December 2021) - Ren, Xiaojun; Cheng, Jiyan; Zhu, Min; Chen, Xiao; Jiang, Min; Hu, Xinmei; Lu, Yanan
Abstract: Circular RNAs (circRNAs) participate in the progression of various cancers. However, the function of circ_0062019 in prostate cancer (PCa) remains unclear. In this study, CCK‐8, colony formation, transwell, tube formation and flow cytometry assays were applied to assess cell proliferation, motility, angiogenesis, cell cycle distribution and apoptosis. The binding association between miR‐1253 and circ_0062019 or NRBP1 was verified through dual‐luciferase reporter assay and RIP assay. Xenograft assay was conducted to evaluate tumour formation in vivo. As a result, circ_0062019 and NRBP1 were increased, but miR‐1253 was decreased in PCa. Depletion of circ_0062019 curbed cell proliferation, migration, invasion, angiogenesis and EMT and induced apoptosis in PCa cells. Circ_0062019 facilitated the malignancy of PCa cells via sequestering miR‐1253. Simultaneously, miR‐1253 hindered PCa cell progression via regulating NRBP1. Ccirc_0062019 silencing suppressed tumour growth in vivo. Taken together, circ_0062019 expedited PCa progression through mediating miR‐1253/NRBP1 pathway.